A needs analysis of oral communication for business students / Savina Kaur Raminderjeet Singh - Savina Kaur , Raminderjeet Singh (2020)
English is a universal language of communication in many industries such as Education, Business, Medical, Finance, Hospitality and Digital World. The present study focuses on the oral communicative needs analysis for business students in one of the private universities in Kuala Lumpur, Malaysia. It was reported that many employers were reluctant to employ fresh graduates due to poor communication in English (Sani, R. The NST, 2019). Therefore, the objectives of this study is to identify three things which are, the English language needs of the Business students and challenges of the business students in English language as well as to propose an English language syllabus pertaining to the workplace. This study utilized a qualitative method (Creswell, 2014) with the distributions of questionnaires to 30 business students and semi-structured interviews to business lecturers and industrial supervisors. The findings show that business students faced major problems in communicating in English language such as, incorrect pronunciations, lack of presentation skills and poor abilities to communicate with colleagues and clients. The findings further revealed that the business students need a specific course module for a Business English course and emphasis has to be on speaking and listening skills pertaining to the workplace. Some suggestions for Business English syllabus suggested by the respondents of this study are, negotiating in various situations, making polite conversations with prospective clients and telephoning skills. It is hoped that the present study would be beneficial for business students to face the real workplace challenges as English language proficiency plays an important role for employment.